2017
DOI: 10.1007/s10571-017-0491-3
|View full text |Cite
|
Sign up to set email alerts
|

Stress-Induced Alterations of Immune Profile in Animals Suffering by Tau Protein-Driven Neurodegeneration

Abstract: Alzheimer's disease (AD) is a multifactorial disorder; neurofibrillary pathology composed of tau protein is found side by side with amyloid-β deposits and extensive neuroinflammation. The immune system of the brain is considered as one of the factors that could influence the speed of the progression of AD neuropathology as a potential mediator of the damage induced by AD protein deposits. Alzheimer's disease pathology can be impacted by psychological stress; however, signalling pathways in background are not w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 99 publications
0
9
0
Order By: Relevance
“…Specifically, the primary roles of IL-6 are largely coupled with the regulation of the other two proinflammatory cytokines IL-1β and TNF-α, and studies have reported that IL-6 often inhibits the expression of IL-1β and TNF-α while promoting IL-10 [90]. This has been suggested to be especially so when in an anti-inflammatory environment, where the integrity of the blood-brain barrier needs to be regulated [91], such as during the occurrence of neuroinflammatory responses.…”
Section: Brain Alterations In Relation To Inflammation and Oxidative mentioning
confidence: 99%
“…Specifically, the primary roles of IL-6 are largely coupled with the regulation of the other two proinflammatory cytokines IL-1β and TNF-α, and studies have reported that IL-6 often inhibits the expression of IL-1β and TNF-α while promoting IL-10 [90]. This has been suggested to be especially so when in an anti-inflammatory environment, where the integrity of the blood-brain barrier needs to be regulated [91], such as during the occurrence of neuroinflammatory responses.…”
Section: Brain Alterations In Relation To Inflammation and Oxidative mentioning
confidence: 99%
“…The MHC also is densely populated with genes related to neuronal signaling and plays a role in immunity. Other genes related to immune functioning (e.g., CX3CR1 , IL23R ) 100 103 also emerged. Study results support multiple etiologic pathways to MD and indicate that complex genetic disorders such as MD likely reflect a large number of independent genetic factors that each contribute a small amount of variance to disease susceptibility and multiple psychiatric diseases likely share genetic risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…However, in our experimental model, there were no significant changes seen in the gene expression of markers studied indicating for the brain immune activity by neuronal CD200 and its microglial receptor CD200R (Yi et al 2012), or suppression of inflammatory cytokines release from microglia mediated by TREM2 (Mecca et al 2018) ( Figure 5). Restricted expression of the chemokine receptor CX3CR1 in microglia (Wolf et al 2013), as one of the stress-responsive gene involved in neuroinflammation accompanying neurodegenerative tau pathology, has been described in rats (Novak et al 2018). But we did not observe any changes in the expression of CX3CR1 in mice cortex indicating for a quiescent "sampling" or surveillance mode of microglia as it has previously been reviewed (Biber et al 2007).…”
Section: Discussionmentioning
confidence: 99%